2015
DOI: 10.1002/anie.201409792
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of O‐ and C‐Glycosylating Variants of the Landomycin Glycosyltransferase LanGT2

Abstract: The structures of the O-glycosyltransferase LanGT2 and the engineered, C—C bond-forming variant LanGT2S8Ac show how the replacement of a single loop can change the functionality of the enzyme. Crystal structures of the enzymes in complex with a nonhydrolyzable nucleotide-sugar analogue revealed that there is a conformational transition to create the binding sites for the aglycon substrate. This induced-fit transition was explored by molecular docking experiments with various aglycon substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 42 publications
(38 reference statements)
1
26
0
Order By: Relevance
“…Therefore, we initially believed that the C-glycosylation activity of AbCGT was also dependent on the acyl group, similar to other known CGTs. However, to our surprise, AbCGT exhibited catalytic activity when phloroglucinol derivatives (20)(21)(22) without acyl groups attached to the aromatic rings were used as substrates ( Supplementary Figs. 34-36).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, we initially believed that the C-glycosylation activity of AbCGT was also dependent on the acyl group, similar to other known CGTs. However, to our surprise, AbCGT exhibited catalytic activity when phloroglucinol derivatives (20)(21)(22) without acyl groups attached to the aromatic rings were used as substrates ( Supplementary Figs. 34-36).…”
Section: Resultsmentioning
confidence: 98%
“…Plant CGTs usually recognize only substrates with the basic core structure of acyl phloroglucinol, which possesses three hydroxyl groups and one acyl group 15,[23][24][25][26]29,31,32 . Thus, to explore the effects of the number and position of phenolic hydroxyl groups on the catalytic activity of AbCGT, an acceptor library containing acyl phenols (1-3), acyl resorcinols (4-9), acyl phloroglucinols (10-19 and 23), phloroglucinol derivatives (20)(21)(22) without basic acyl groups, and coumarins (24)(25)(26) was used for the reactions (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LanGT2 has been engineered to catalyze C‐glycosylation through exchange of just 12 residues in the α3‐helix from the UrdGT2 template . The modification led to reduction in the size of the aglycone binding pocket in LanGT2 particularly by I58 and I62 . Docking studies indicated that subtle repositioning of the aglycone relative to the sugar nucleotide, with the C9 atom moving toward the cosubstrate and the C8 hydroxyl group away from the cosubstrate, leading to a switch in regiochemistry and even the catalytic mechanism of LanGT2 .…”
Section: Direct Modulation Of Enzyme Function In Biosynthetic Gene CLmentioning
confidence: 99%
“…Surprisingly, multiple sequence comparison also revealed high homology of SchS7 to a known O‐GT, LanGT2 from S. cyanogenus , which catalyzes the first glycosylation step by attaching activated d ‐olivose to 8‐OH of the aglycone . Interestingly, an engineered version of LanGT2 was able to act as a C‐GT, showing activity for both C‐ and O‐glycosylation similar to UrdGT2 . Therefore, we expected SchS7 to be responsible for the attachment of d ‐amicetose to C‐9 of the polyketide aglycone.…”
Section: Discussionmentioning
confidence: 99%